Structural Modifications Yield Novel Insights Into the Intriguing Pharmacodynamic Potential of Anti-inflammatory Nitro-Fatty Acids - Hellmuth, Nadine; Brat, Camilla; Awad, Omar; George, Sven; Kahnt, Astrid; Bauer, Tom; Huynh Phuoc, Hai Phong; Steinhilber, Dieter; Angioni, Carlo; Hassan, Mohamed; Hock, Katharina J.; Manolikakes, Georg; et al. (Frontiers in Pharmacology, 2021)
Endogenous nitro-fatty acids (NFA) are potent electrophilic lipid mediators that exert biological effects in vitro and in vivo via selective covalent modification of thiol-containing target proteins. The cytoprotective, anti-inflammatory, and anti-tumorigenic effects of NFA in animal models of disease caused by targeted protein nitroalkylation are a valuable basis for the development of future anti-phlogistic and antineoplastic drugs. Considering the complexity of diseases and accompanying comorbidities there is an urgent need for clinically effective multifunctional drugs. NFA are composed of a fatty acid backbone containing a nitroalkene moiety triggering Michael addition reactions. However, less is known about the target-specific structure–activity relationships and selectivities comparing different NFA targets. Therefore, we analyzed 15 NFA derivatives and compared them with the lead structure 9-nitro-oleic acid (9NOA) in terms of their effect on NF-B (nuclear factor kappa B) signaling inhibition, induction of Nrf-2 (nuclear factor erythroid 2-related factor 2) gene expression, sEH (soluble epoxide hydrolase), LO (lipoxygenase), and COX-2 (cyclooxygenase-2) inhibition, and their cytotoxic effects on colorectal cancer cells. Minor modifications of the Michael acceptor position and variation of the chain length led to drugs showing increased target preference or enhanced multi-targeting, partly with higher potency than 9NOA. This study is a significant step forward to better understanding the biology of NFA and to the development of their enormous potential as scaffolds for designing future anti-inflammatory drugs.